Pandemia Covid-19 și creșterea riscurilor sociale pentru persoanele în vârstă - Gagauz, Olga; Buciuceanu-Vrabie, Mariana; Tabac, Tatiana (Calitatea Vieții, 2021)
The paper focuses on assessing the situation of older persons in the Republic of Moldova, in the context of the COVID-19 pandemic. The social diagnosis of the structural, institutional, community and intergenerational openness to the needs of this category of population highlights the pandemic challenges it faces. The methodology of the study is based on the results of the qualitative study conducted in August−September 2020 and April−May 2021 with the older people, local public administration and social workers. Through empirically reasoned findings, the paper updates the main difficulties encountered in the context of the pandemic and the depth of the social impact on the older people at community level. In addition to the direct risk to physical health, the exclusion and discrimination of the older people increased during the COVID-19 pandemic, there has been an increased risk of violence and neglect, and cases of stigma at community level. The individual/family resources of the older people, especially in the case of COVID-19 infection and treatment, have played an important role in overcoming the crisis. The consequences of COVID-19 are associated with a worsening of the health of the elderly and an increase in the need for medical services. “Ageist” attitudes also occurred in the post-quarantine period, undermining the rights of older people to quality services. Thus, the need for continuous monitoring of the situation and combating "ageist" attitudes in the post-pandemic period is emphasized.